2021
DOI: 10.1002/anbr.202100082
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Cyclodextrin‐Based Nanoparticulate Vaccines Can Trigger T‐Cell Immune Responses

Abstract: Particulate antigen‐delivery systems are instrumental for therapeutic vaccination, aiming at improving the safety and efficacy of treatments by targeting specialized antigen‐presenting cells (APCs). However, the induction of potent adaptive immune responses, especially cellular immunity, remains a major challenge. Herein, a novel nanoparticulate antigen‐delivery system based on amphiphilic cyclodextrins (CDs) is developed as a platform for therapeutic cancer vaccination. Supramolecular nanosized CD structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The thioether derivative heptakis-(6-deoxy-6-hexylthio)-β-cyclodextrin (CDSC 6 , Scheme , 3) was obtained from native β-CD by bromination and subsequent nucleophilic substitution with 1-hexanethiol , with a yield >50%. The 1 H NMR spectrum (Figure C) confirms the conjugation of the alkyl protons H7–19 (δ 0.863–3.327 ppm).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The thioether derivative heptakis-(6-deoxy-6-hexylthio)-β-cyclodextrin (CDSC 6 , Scheme , 3) was obtained from native β-CD by bromination and subsequent nucleophilic substitution with 1-hexanethiol , with a yield >50%. The 1 H NMR spectrum (Figure C) confirms the conjugation of the alkyl protons H7–19 (δ 0.863–3.327 ppm).…”
Section: Resultsmentioning
confidence: 99%
“…While hydrophobic molecules can be incorporated in the hydrophobic cavity of the CD structure by forming inclusion complexes, the complexation of hydrophilic compounds is also possible . Further, amphiphilic CD nanoparticles encapsulating small molecules, such as chemotherapeutic agents, ,, as well as biomacromolecules, such as genes or peptide antigens, , have been reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that mice immunized with peptide-loaded CD nanoparticles have higher frequencies of antigen-specific and cytokine-producing CD8+ T cells. Contrary to peptide-loaded CD nanoparticles, the blank CD nanoparticles did not cause changes in the CD80 or CD86 levels, and based on this result, it was stated that amphiphilic CD nanoparticles are safe to use as a carrier system in vaccines [86].…”
Section: Cyclodextrins As Nano-sized Carrier Systemsmentioning
confidence: 91%